KEEFEKTIFAN MODEL PEMBELAJARAN KOOPERATIF TIPE CIRC (COOPERATIVE INTEGRATED READING AND COMPOSITION) TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS IV SD NEGERI KEDUNGUTER 02 BREBES - Mudzanatun Mudzanatun; Iswatun Fauziah (Universitas PGRI Semarang, 2013)
This research is motivated to improve the quality of education according to the standard of competence specified, the system needs to be implemented better learning outcomes assessment and planned mainly on mathematics learning. The demands of the curriculum resulted in learning mathematics is still fixated theory, so that students become less creative, less formal, and is still fixated on the standard formula. In addition, the learning model which uses only one-way learning model is less effective and less efficient. The problems revealed in this study is the use of the model is the CIRC (Cooperative Integrated Reading and Composition) mathematics effectively improve learning outcomes. Goals to be achieved in this study was to determine the effectiveness of the model CIRC (Cooperative Integrated Reading and Composition) in improving student learning outcomes in mathematics IV.Penelitian class was held at the Bradford Elementary School Kedunguter 02 in the school year 2012/2013. Variable in this study is the result of student learning in mathematics learning is the dependent variable (Y) and learning model CIRC (Cooperative Integrated Reading and Composition) which is the independent variable (X). While the failed hypothesis H0 is rejected if t <t table or it can be said that the cooperative model of CIRC is not effective against math hasilbelajar Elementary School fourth grade students Kedunguter 02 Bradford, and H1 is accepted if t ?óÔÇ??Ñ t table or it can be said that the cooperative model of CIRC effective against learning outcomes fourth grade math students Kedunguter 02 Bradford District.This type of research is experimental. The population in this study were fourth grade students Kedunguter 02 Bradford Elementary School in 2012/2013 the number of 40 students. Samples taken a total sample of 40 students. Desainpenelitian used was a pretest-posttest control group design. Based on the analysis of data after getting treatment, menunjukkanbahwa mathematics achievement using cooperative learning model CIRC (Cooperative Integrated Reading and Composition) can achieve mastery learning classical study sebesar75%. Data were analyzed using the statistical analysis t-test. Based on calculations using t-test at significance level (?Ä??) = 0.05, obtained t count> t table ie 2.0757> 1.68, so the null hypothesis (H0) is rejected and the alternative hypothesis (H1) is accepted, it can be concluded cooperative learning model type CIRC effective on students' mathematics learning outcomes.